The green house effect climate change and global warming - Reeds, Rod ([Australia] : Rees films, 2007)
The DVD contains a basic version suitable for all students from senior primary on, and also offers an advanced version for senior secondary students, with in depth analysis of greenhouse gases and their effects. In addition, there are fascinating extras: ice-core research in Antarctica, how warming threatens coral reefs, carbon capture and storage - how it works
Basic version (suitable for all levels) -- Advanced version (more analysis on greenhouse gases) -- Extras
Title from title screen
Narration: Cath Leslie
DVD Format
Keywords: Global warming; Greenhouse effect, Atmospheric; Climatic changes; Risk perception